Low Infection Rates in Total Knee Arthroplasty in End Stage Renal Failure Patients - Ling, Zhixing Marcus; Soong, Jun Wei; Loh, Bryan; Yeo, Seng Jin; Pang, Hee Nee; Lo, Ngai Nung (The Journal of arthroplasty, 2016)
End stage renal failure is considered a risk factor for postoperative infection and many surgeons are cautious in offering this group of patients total knee arthroplasty for symptomatic osteoarthritis. In this retrospective study, 16 total knee arthroplasties were performed in 13 patients and each case was followed up for an average of 5.1years. We report no cases of infection and also an overall improvement in multiple validated outcome measures. There were, however, 2 cases of periprosthetic loosening. As the patients in our series were generally younger and none was diagnosed with stroke or peripheral vascular disease at the time of surgery, we believe that careful patient selection is key to reducing infection rates in this challenging group of patients.